Continuous improvement and innovation - Gersten, Frank; Riis, Jens O. (Integrated manufacturing systems ;, 2002)
If we want everything to remain as it is, it willbe necessary for everything to change(Giuseppe Tomasi Di Lampedusa (1896-1957), Sicilian author). Over the last two decades, the externaldynamics of industrial firms have increasedconsiderably in terms of market andtechnological change.